Conserved upstream sequences of human class II major histocompatibility genes enhance expression of class II genes in wild-type but not mutant B-cell lines. - Sloan, J H (1988)
Class II major histocompatibility genes contain a conserved upstream sequence (CUS) that is important in the expression of these genes. This region has been divided into two major elements, the X box and the Y box. The ability of these elements to mediate transcription of a heterologous promoter was assayed upon transfection into a B-cell line (Raji), a class II-specific trans-acting factor-deficient B-cell line (RJ2.2.5 cells), and a T-cell line (Jurkat). The results showed that the X box element was responsible for directing tissue-specific expression when Raji cells were compared to Jurkat cells. The X box could not direct expression of the heterologous promoter in the trans-acting factor-deficient cell line, indicating that the X box is an ultimate target of the missing or defective factor in the RJ2.2.5 cell line. The Y box directed an equal but extremely low level of transcription in this system in both the mutant and wild-type B-cell lines, suggesting that this element is not involved in B-cell expression or as a target of the mutant factor.